Hubungan antara Stres Kerja dengan Komitmen Organisasi pada Karyawan bagian Produksi di PT.X - Oya, Adhisty Merrial; Kurniawan, Jimmy Ellya (Psychopreneur Journal, 2019)
Turnover often occur. This is because of low organizational commitment, and low organizational commitment occurs because of work stress. Production employees have high work stress because they have a workload and work risk who can make low commitmnes and occur turnover. The purpose of this study was to determine the relationship between work stress and organizational commitment. Hypothesis of this study is there is a negative relationship between work stress and organizational commitment of production employee in PT.X. The subjects in this study were 63 production employees at PT.X. This study used quantitative method with correlational design. Data were collected using work stress scale that has been adapted from Parker & Decotis (1983) and organizational scale that has been adapted from Allen dan Meyer (1990). The results showed that there is no relationship between work stress and organizational commitment of production employee in PT.X (ρ=0.000 ; (p > 0.05)